Operation Sense - Karama, Muneer Jebreel (My University, 2003)
The aim of this article is to develop the issue of operation sense of fractions through the conditions in real-world for the students in 7th grade, so this advancing students’ mathematical thinking in every day mathematics lessons , which necessary for developing , and improving the higher order thinking skills for the students’.
Developing operation sense
Keywords: Operation sense ,Number sense , Fractions , Addition , Subtraction, Division , Multiplication , Real-world , 7th grad .